Trypanosoma evansi Infection in Sumba Horses in East Sumba Regency : A Study at BBVet Denpasar - Sarwo Edy Wibowo; Fahmida Manin; Anie Insulistyowati; Fadel Muhammad Priyatna; Yudhi Ratna Nugraheni; Paradewa Baskara; Aan Awaludin (Journal of Applied Veterinary Science And Technology, 2024)
Background: Sumba is one of the original habitats of the Sandalwood Ponies and the presence of pony is an important element for the community. The Sumbanese herd their ponies in the savanna and rely on nature as a source of horse feed, consequently, during the dry season, the availability of the feed decreases. These conditions can potentially reduce the health status of ponies and increase morbidity or mortality from diseases caused by Trypanosoma evansi. Purpose: This study aims to determine the occurrence and intensity of Trypanosoma evansi infection in blood samples from horses examined at the Denpasar Bali Veterinary Centre. Methods: Thirty blood samples were collected from East Sumba Regency. Three milliliters of blood were taken from the jugular vein and immediately transferred into an ethylenediaminetetraacetic acid tube. Thin blood smears were subsequently prepared and examined using the Giemsa-stained blood smears method. The preparations of blood smear were examined under microscope to determine the Trypanosoma evansi infection and the intensity was calculated on the average number of Trypanosoma evansi in 100 red blood cells. Results: The result showed that six out of 30 horses were tested positive for Trypanosoma evansi. The infection intensity ranged from two to 18 parasites with an average number of 8 in the blood smear examination method. Conclusion: The incidence of trypanosomiasis in Sumba horses varies with each season in East Sumba Regency. The prophylactic measures that should be adopted in the particular herd of horses because this is the most significant blood protozoan parasite of equines.